LOX-1 (Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1) Deletion Has Protective Effects on Stroke in the Genetic Background of Stroke-Prone Spontaneously Hypertensive Rat. Issue 6 (June 2020) - Liang, Yi-Qiang; Kakino, Akemi; Matsuzaka, Yasunari; Mashimo, Tomoji; Isono, Masato; Akamatsu, Tomohisa; Shimizu, Hana; Tajima, Michiko; Kaneko, Takehito; Li, Lei; Takeuchi, Fumihiko; Sawamura, Tatsuya; et al.
Abstract : Background and Purpose—: oxLDL (oxidized low-density lipoprotein) has been known for its potential to induce endothelial dysfunction and used as a major serological marker of oxidative stress. Recently, LOX-1 (lectin-like oxidized low-density lipoprotein receptor-1), a lectin-like receptor for oxLDL, has attracted attention in studies of neuronal apoptosis and stroke. We aim to investigate the impact of LOX-1 -deficiency on spontaneous hypertension-related brain damage in the present study. Methods—: We generated a LOX-1 deficient strain on the genetic background of stroke-prone spontaneously hypertensive rat (SHRSP), an animal model of severe hypertension and spontaneous stroke. In this new disease model with stroke-proneness, we monitored the occurrence of brain abnormalities with and without salt loading by multiple procedures including T 2 weighted magnetic resonance imaging and also explored circulatory miRNAs as diagnostic biomarkers for cerebral ischemic injury by microarray analysis. Results—: Both T 2 weighted magnetic resonance imaging abnormalities and physiological parameter changes could be detected at significantly delayed timing in LOX-1 knockout rats compared with wild-type SHRSP, in either case of normal rat chow and salt loading ( P <0.005 in all instances; n=11–20 for SHRSP and n=13–23 for LOX-1 knockout rats). There were no significant differences in the form of magnetic resonance imaging findings between the strains. A number of miRNAs expressed in the normal rat plasma, including rno-miR-150-5p and rno-miR-320-3p, showed significant changes after spontaneous brain damage in SHRSP, whereas the corresponding changes were modest or almost unnoticeable in LOX-1 knockout rats. There appeared to be the lessening of correlation of postischemic miRNA alterations between the injured brain tissue and plasma in LOX-1 knockout rats. Conclusions—: Our data show that deficiency of LOX-1 has a protective effect on spontaneous brain damage in a newly generated LOX-1 -deficient strain of SHRSP. Further, our analysis of miRNAs as biomarkers for ischemic brain damage supports a potential involvement of LOX-1 in blood brain barrier disruption after cerebral ischemia. Abstract : Supplemental Digital Content is available in the text.